Kontribusi Celebrity Worship terhadap Pembelian Impulsif Remaja Penggemar K-Pop - Tenga Araminta Nadia Riwu Kaho; R. Pasifikus Ch. Wijaya; Juliana M.Y. Benu (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the dimensions of the absorption contribution of celebrity adoration to the impulsive buying behavior of young K-Pop fans, to determine the dimensions of the contribution of addiction to celebrity worship to the impulsive buying behavior of young K-Pop fans, to determine the contribution of absorption and addiction to celebrity worship. as a whole on the impulsive buying behavior of adolescent K-Pop fans. The population in this study is all K-popers in Indonesia with statistical results showing a proportion of 23% of the 100 million K-popers in the world. In this study using a non-probability sampling technique, namely purposive sampling. This type of research is quantitative. The research results show that celebrity worship behavior contributes to the impulsive buying behavior of young K-Pop fans with a sample of 258 teenagers spread across several islands in Indonesia. The absorption dimension contributed 32.5% to the impulsive buying behavior of young K-Pop fans while the addiction dimension contributed 30.7% to the impulsive buying behavior of young K-Pop fans. Celebrity worship uses the F test to see the overall effect on consumptive behavior, namely the celebrity worship variable (absorption and addiction) has a significant influence on adolescent impulsive buying behavior in purchasing products related to idols of 63.2% and the remaining 36.8 % influenced by other factors.